Technology research and construction scheme of unified data lake - Zhiyong LIU; Zhongjiang HE; Jinglong LIU; Yilong RUAN; Zhaofang MENG (Dianxin kexue)
From the requirements of enterprise digital transformation and the challenges faced by big data platform, the construction ideas and principles of unified data lake were expounded.A unifid data lake construction scheme based on BSS/MSS/OSS cross domain fusion was proposed, which adopted logical unification, physical dispersion, unified data directory, unified security management and application of decoupling fusion.The construction practice of unified data lake was described in recent two years.